HUBUNGAN PERSEPSI ORANG TUA TENTANG MAKANAN KEMASAN DENGAN KESEHATAN FISIK ANAK USIA 4-6 TAHUN DI TK RAM NU BAYEMAN KABUPATEN LUMAJANG - Utami, Novita Wahyu; Nur Endah, Yessy; Zakiyyah, Muthmainah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Parents have an important role in the pattern of food or snacks chosen by their children because they have a big influence on the physical health or nutritional status of children. The purpose of this study was to determine the relationship be- tween parents' perceptions of packaged snacks and the physical health of children aged 4-6 years at RAM NU Kindergarten, Bayeman. The cross-sectional research design was used with 34 respondents, namely parents and children at RAM NU Bayeman Kindergarten, Lumajang Regency. The measuring instrument in this study was the respondent characteristic questionnaire. Chi-square test was used to answer the purpose of this study. The results showed that the majority of par- ents had a negative perception of packaged snacks as many as 19 respondents (56%). the majority of children aged 4-6 years in RAM TK NU Bayeman have healthy physical health as many as 22 respondents (66%). There is no significant correlation between parents' perceptions of packaged snacks and the physical health of children aged 4-6 years in TK RAM NU Bayeman, Luamajang, namely p-value 0.35. This is because parents have a negative perception of packaged snacks, adequate knowledge of information about packaged foods, nutritional value and the impact that occurs when consuming packaged snacks will affect health. So that it leads to careful behavior in choosing and consuming snacks for their children. Because at the age of 4-6 years children are still under parental monitoring and control of what foods are consumed. .